Reliability payments to generation capacity in electricity markets - Olsina, Fernando Gabriel (2014)
Electric power is a critical input to modern economies. Generation adequacy and security of supply in power systems running under competition are currently topics of high concern for consumers, regulators and governments. In a market setting, generation investments and adequacy can only be achieved by an appropriate regulatory framework that sets efficient remuneration to power capacity. Theoretically, energy-only electricity markets are efficient and no additional mechanism is needed. Nonetheless, the energy-only market design suffers from serious drawbacks. Therefore, jointly with the evolution of electricity markets, many remunerating mechanisms for generation capacity have been proposed. Explicit capacity payment was the first remunerating approach implemented and perhaps still the most applied. However, this price-based regulation has been applied no without severe difficulties and criticism. In this paper, a new reliability payment mechanism is envisioned. Capacity of each generating unit is paid according to its effective contribution to overall system reliability. The proposed scheme has many attractive features and preserves the theoretical efficiency properties of energy-only markets. Fairness, incentive compatibility, market power mitigation and settlement rules are investigated in this work. The article also examines the requirements for system data and models in order to implement the proposed capacity mechanism. A numerical example on a real hydrothermal system serves for illustrating the practicability of the proposed approach and the resulting reliability payments to the generation units.